Double-push skating and klap-skate in cross country skiing, technical developments for the future? - Stöggl, T.; Lindinger, S. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Two technical developments in XC-skiing, the klap-system and the double-push (DPU), were developed in the last years. Kinematic, kinetic and electromyographic measurements at maximal speed using the one-skate were performed to compare these developments towards the conventional technique or material. In both, DPU and klap-system, athletes were able to complete a 50m measurement track faster (up to 0.40 sec). DPU was characterized by higher muscle activity, higher angular velocities, and higher lateral foot forces especially in gliding phase. With the klap-system higher peak foot forces (up to 300N), higher lateral foot forces (more than 100%), and a more lateral course of the center of pressure over the whole push-off occurred. The main advantages of the DPU can be seen in the additional second push-off instead of passive gliding, and the in direct line of the forward movement set ski for the first push-off. The possibility to use a totally stiff boot with the klap system leads to less loss of force and energy, and a better distributed force application during push-off.